Proyecto de inversión para la producción y comercialización de productos derivados del banano (banano recubierto de chocolate con aderezos y dulce de banano) en el mercado ecuatoriano - Veliz Gonzalez, Betsabe Eliana (2009)
This is an investment project that is based on the creation, production and commercialization of derived products of the banana, having as main products the banana recovered by chocolate called “ChocoBanana”, and a dessert call “Sweet of Banana”, which are not in the supermarkets, and they are not marketed internally in the country, putting to the consumer's disposition a different alternative in flavor and presentation. The derived products of the banana, they are those that can be elaborated with green or mature banana, in this case mature banana it will be used, where a process will be continued for the elaboration of each product with a strict control of quality. The “ChocoBanana” has a value added in front of those that elaborate other companies that are the seasonings, since inside the Ecuadorian market there is not company that uses them in the “ChocoBanana”; for that which is had the necessary and enough knowledge as for the production refers. The products are presented like functional food by way of cold snack “ChocoBanana”, and of dessert “Sweet of Banana”, standing out the benefits of the banana like matter prevails in whose description finds its high nutritious value, based on a healthy diet for the consumer, in which will be potassium, glucose, vitamin A, B6, B12, iron among others.